METHOD AND GAS DISCHARGE VISUALIZATION TOOL FOR ANALYZING LIQUID-PHASE BIOLOGICAL OBJECTS - Kulyk, Yaroslav A.; Knysh, Bohdan P.; Maslii, Roman V.; Kvyetnyy, Roman N.; Shcherba, Valentyna V.; Kulyk, Anatoliy Ia. (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
In the article are presented the results of researches that touch the problem of the reliability improvement of determining the impurities concentration in biological objects in liquid by using the method of gas discharge visualization. There is an improved analysis method for biological objects in liquid based on gas discharge visualization (GDV), proposed criteria approach towards the assessment of liquid bio object’s composition applying this method, presented the assessment of the nature of liquid bio objects, which use the intensity of spectral components of its radiation has gotten during GDV. There is a developed and researched math model of ignition of a crown discharge and the dependency of spectrum intensity of radiation of liquid-phase biological object on its chemical composition proposed a conversion function for the assessment of the impurities concentration, together with the informative parameters of GDV images. All the results of the experimental researches of GDV and spectral composition of liquid-phase biological objects (LPBO) are presented in the article. The proposed approach lets specify the range of Mg concentrations in an oral fluid (OF) at various thyroid disorders obtained by the trilonometric method. It was found that the concentration of Mg in oral fluid of patients without thyroid disease is 12.73 ± 2.16 mg/l, patients with risk factors for thyroid disease have a concentration of 14.98 ± 1.92 mg/l, patients with sporadic goiter have a concentration of 26.65 ± 3.73 mg/l. Such data allow providing the patients with a better diagnosis of pathological disorders in glandular thyroids that are based on the concentration of Mg in oral fluid. It is confirmed that the concentration of Mg in oral fluid greater than 15 mg/l may indicate the presence of trilonometric pathology, including the focal thyroid gland.